A curcumin-based NIR fluorescence probe for detection of amyloid-beta (Aβ) plaques in Alzheimer's disease. (April 2019) - Si, Guofu; Zhou, Shujie; Xu, Guoyong; Wang, Jiafeng; Wu, Baoxing; Zhou, Shuangsheng
Abstract: Amyloid-beta (Aβ) peptide as one of the main components of senile plaques is closely related to the onset and progression of incurable Alzheimer's disease (AD). In recent years, it is reported that curcumin derivatives have been used as the near-infrared (NIR) fluorescence imaging probes of Aβ plaques for the early diagnosis of AD. To further develop a curcumin-based NIR fluorescent probe for Aβ plaques, in this work, we have synthesized three novel curcumin-based NIR Dyes. Among them, the curcumin derivative Dye 2 showed a significant enhancement in its fluorescence intensity (λem, 635 nm; 19.5-fold increase in quantum yield, Φ = 0.36; Kd, 1.13 μM) after binding to Aβ plaques. Additionally, in vitro and in vivo fluorescence imaging of Aβ plaques strained with Dye 2 confirmed that the compound was a potential probe to detect Aβ plaques in AD. This work opens a perspective to rationally design novel curcumin-based NIR compound for Aβ detection. Highlights: Three novel compounds curcumin-based was synthesized. These compounds shown obvious fluorescence change after binding to Aβ plaques. These compounds have Cytotoxicity. Imaging strained with Dye 2 confirmed that it could be to detect Aβ plaques in AD.